A. A. Navis - Adilla, Ivan (Grasindo, 2003)
Criticism on novels and short stories written by A.A. Navis, an Indonesian prominent writer from Padangpanjang, West Sumatera
Includes bibliographical references (p. 222-226)
Keywords: Navis; A. A.; Authors; Indonesian